ANALISIS FAKTOR PEMBERDAYAAN EKONOMI MASYARAKAT SEKITAR PESANTREN - Ahmad Munib Syafa’at; Nur Anim Jauhariyah (STAI AN-NAJAH INDONESIA MANDIRI, 2022)
Community economic empowerment in this study is an effort to optimize the function of Islamic boarding schools to increase the economic income of the community around the pesantren. The purpose of this study was to analyze the economic empowerment factors of the community around the Darussalam Blokagung Banyuwangi Islamic Boarding School. This study uses a quantitative approach with the data used are primary and secondary data. The research sampling technique was randomized to 108 research respondents. Analysis using path analysis with the help of IBM SPSS software. The results of the analysis show that the variable that has the dominant influence value between strength, weakness, opportunity, and threat to people's income is the strength variable with a contribution of 19.18%, the second is the contribution of the Threat variable of 1.02%, the magnitude of the Weakness contribution of 0.9%, and finally the opportunity contribution of 0.1%. The overall contribution is 22.2%. the remaining 77.8% was influenced by other factors that could not be explained in the study. Keywords: Economic Empowerment, Community, Islamic Boarding School, Path Analysis References Adnan, A. Z. 2018. Strategi Mewujudkan Kemandirian Dalam Pengembangan Dan Pemberdayaan Ekonomi Santri (Studi Kasus di Pondok Pesantren Al Bahjah Cirebon). Syntax Literate : Jurnal Ilmiah Indonesia, Ahmad Faozan, 2006. Pondok Pesantren dan Pemberdayaan Ekonomi. Ibda’: Jurnal Studi Islam dan Budaya, Vol 4, No. 1, 88-102. Arifin, Z. 2012. Perkembangan Pesantren Di Indonesia. Pendidikan Agama Islam Bungin, Burhan. 2005. Metodologi Penelitian Kuantitatif Komunikasi, Ekonomi, Dan Kebijakan Publik Ilmu-ilmu Sosial Lainya. Jakarta: Kencana Creswell, J. 2003. Research design: Qualitative, quantitative and mixed methods approaches (2nd ed.). Thousand Oaks, CA: SAGE Publications. Friedmann.1992. Empowement: the Politics of Alternative Development. Cambridge Mass: Blackwell Publisher Fuad, A. Jauhar. 2012. Pendidikan Karakter Dalam Pesantren Tasawuf. Jurnal Pemikiran Keislaman Irawan dan M.Suparmoko, 2008. Ekonomika Pembangunan. Edisi Keenam, Cet. Kedua, Yogyakarta: BPFE, h. 308 John R. Dew, 1997. Empowerment And Democracy In The Workplace: Applying Adult Education Theory and Practice for Cultivating Empowerment . ISBN 1-5672O-094-X (alk. paper). United States of America: Quorum Books. Johnson, Richard A., & Dean W. Wichern (1992). Applied Multivariate Statitical Analysis. New Jesrsey: Prentice Hall. Engewood Cliffs. Juanda, Bambang. 2009. Metodologi Penelitian Ekonomi & Bisnis. Bogor: IPB Press. Karel A. Steenbrink. 1994. Pesantren, Sekolah dan Madrasah, Pendidikan Islam dalam Kurun Modern. Jakarta: LP3ES. Kartasasmita, G., 1996. Pembangunan Untuk Rakyat: Memadukan Pertumbuhan dan Pemerataan. Jakarta: PT. Pustaka Cidesindo. Khan, Abdul Rashid & Zainab Bibi. 2016. Women's Socio-Economic Empowerment Through Participatory Approach: A Critical Assessment, Pakistan Economic and Social Review, Vol. 49, No. 1 (Summer 2011), pp. 133-148, Stable URL: http://www.jstor.org/stable/41762427. PermenDesaPDTT 17 tahun 2019 tentang Pedoman Umum Pembangunan dan Pemberdayaan Masyarakat Desa Pondok Pesantren Darussalam. 2019. Profil Yayasan Pondok Pesantren Darussalam Blokagung Karangdoro Tegalsari Banyuwangi. Darussalam Press Rangkuti, Freddy. 2009. Strategi Promosi Yang Kreatif. edisi pertama, cetakan pertama, Penerbit : Gramedia Pustaka Utama, Jakarta Rangkuti, Freddy. 2013. SWOT Balance Scorecard. Cetakan keempat Gramedia Pustaka Utama. Sugiyono. 2007. Metode Penelitian Kuantitatif Kualitatif dan R&D. Bandung: Alfabeta Sumodiningrat, G. 1998. Membangun Perekonomian Rakyat. Yogyakarta: Pustaka Pelajar. hlm. 24 Sumodiningrat, G.1999. Pemberdayaan Masyarakat dan Jaring Pengamanan Sosial. Yogyakarta: Ghalia Indonesia, 133-134. Soedjatmoko, 2000. Masalah Sosial Budaya. Yogyakarta: Tiara Wacana. h. 6-8. Soerjono Soekanto, 1993. Beberapa Teori Sosiologi Tentang Struktur Masyarakat, Cetakan Kedua. Jakarta: PT Raja Grafindo Persada Suharto, Edi. 2010. Membangun Masyarakat Memberdayakan Rakyat, Bandung: Refika Aditama. Surakhmad, Winarno. 2004. Pengantar Penelitian Ilmiah Dasar Metode Teknik. Bandung: Tarsito Suryana, 2000. Ekonomi Pembangunan Problematika dan Pendekatan, Edisi Pertama. Jakarta: Selemba Empat. Toyin Falola and Jamaine Abidogun. 2014. Education, creativity, and economic empowerment in Africa. First published in 2014 by Palgrave Macmillan® in the United States—a division of St. Martin’s Press LLC, 175 Fifth Avenue, New York, NY 10010. ISBN 978-1-349-49395-1 ISBN 978-1-137-43850-8 (eBook). DOI 10.1057/9781137438508 Mardi Yatmo Hutomo, 2000, Pemberdayaan Masyarkat dalam Bidang Ekonomi : Tinjauan Teoritik dan Implementasi, Naskah No.20 Juni-Juli Mardikanto, M. dan Soebiato, P. 2015. Pemberdayaan Masyarakat dalam Perspektif Kebijakan Publik, Cet. Ke-3. Bandung: Alfabeta, h.23. Mertokusumo, S. 2010. Suatu Pengantar. Yogyakarta: Cahaya Atma Pustaka. Mubyarto. 1996. Ekonomi Rakyat dan Program IDT, Yogyakarta: Adtya Media. Mubyarto. 2000. Membangun Sistem Ekonomi. Yogyakarta: BPFE, 263-264 Muchsin, M. Bashori, Yuli Andi Gani, dan M. Irfan Islamy. 2009. Upaya Pondok Pesantren Dalam Pemberdayaan Masyarakat Sekitar Hutan.Wacana : Jurnal Ilmu Pengetahuan Budaya. Vol. 12 No. 2 April 2009. http://wacana.ui.ac.id/index.php/wjhi/issue/archive Mulyawan, R. 2016. Masyarakat, Wilayah, dan Pembangunan. Bandung: Unpad Press. Muslim, A. 2009. Metodologi Pengembangan Masyarakat, Yogyakarta: Teras, 2009. Muttaqin, R. 2011. Kemandirian Dan Pemberdayaan Ekonomi Berbasis Pesantren (Studi atas Peran Pondok Pesantren Al-Ittifaq Kecamatan Rancabali Kabupaten Bandung terhadap Kemandirian Ekonomi Santri dan Pemberdayaan Ekonomi Masyarakat Sekitarnya). JESI (Jurnal Ekonomi Syariah Indonesia) Vol 2 No 1 Desember 2011. http://ejournal.almaata.ac.id/index.php/JESI/article/view/134 DOI: http://dx.doi.org/10.21927/jesi.2011.1(2).65-94 Mochtar, Buchori. 1994. Spektrum Problematika Pendidikan di Indonesia, cet. Ke-1. Yogyakarta: Tiara Wacana Yogya. Nadzir, Mohammad. 2015. Membangun Pemberdayaan Ekonomi di Pesantren. Economic, Jurnal Ekonomi Islam Volume VI/ Edisi 1/ Mei 2015. http://journal.walisongo.ac.id/index.php/economica/article/view/785. Doi: 10.211580/economica.2015.6.1.785 Ndraha, Taliziduhu. 1981. Partisipasi Masyarakat Desa dalam Pembangunan Desa. Jakarta : Yayasan Dharma IIP. Ryandono, M. N. H. 2018. Peran Pondok Pesantren dalam Pemberdayaan Sosial Ekonomi di Jawa Timur pada Abad ke-20. Jurnal Mozaik Humaniora Vol 18, No 2 (2018). https://e-journal.unair.ac.id/MOZAIK/article/view/10934 Doi: 10.20473/mozaik.v18i2.10934 Undang-Undang Dasar Negara Republik Indonesia 1945 dengan Penjelasannya, Surabaya: CV Cahaya Agency, 2014, h.108. Undang-undang No 6 Tahun 2014 Tentang Desa Undang-Undang Republik Indonesia Nomor 18 Tahun 2019 Tentang Pesantren